2006
DOI: 10.1183/09031936.06.00008005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clarithromycin on rhinovirus-16 infection in A549 cells

Abstract: Clarithromycin (CM) has been found to inhibit the production of the intercellular adhesion molecule (ICAM)-1 and the secretion of interleukin (IL)-6 and IL-8, which may have beneficial effects on the pathophysiological changes related to rhinovirus (RV) infection. The effect of CM on RV infection in A549 cells was therefore investigated.Cells were pre-treated with 1, 10 or 100 mM CM, either starting 3 days before infection and continuing thereafter, or by addition at the time of infection. RV titre, as measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 29 publications
3
58
2
3
Order By: Relevance
“…In our study, we further demonstrated that azithromycin treatment had antiviral properties characterised by a seven-fold reduced RV1B replication in CF bronchial cells. Our findings confirm previous observations showing antiviral properties of macrolides such as azithromycin [12], erythromycin [10], clarithromycin [9] and bafilomycin A1 [11] in RV-infected airway epithelial cells. In addition, we observed that the decreased RV1B load after azithromycin treatment was not attributable to azithromycin-induced cytotoxicity.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In our study, we further demonstrated that azithromycin treatment had antiviral properties characterised by a seven-fold reduced RV1B replication in CF bronchial cells. Our findings confirm previous observations showing antiviral properties of macrolides such as azithromycin [12], erythromycin [10], clarithromycin [9] and bafilomycin A1 [11] in RV-infected airway epithelial cells. In addition, we observed that the decreased RV1B load after azithromycin treatment was not attributable to azithromycin-induced cytotoxicity.…”
Section: Discussionsupporting
confidence: 82%
“…cell adhesion molecule 1, which is the cell surface entry receptor for the major group of RVs, as a possible anti-RV mechanism of macrolide treatment [9][10][11]. Interestingly, this suggests that macrolides have antiviral effects on both minor-and major-type RV infection independently of the expression of the respective surface entry receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen-membered-ring macrolides, such as erythromycin and clarithromycin, have been reported to reduce the titers of rhinovirus and influenza virus and the cytokine response induced by these viruses (14,31,33). Our results indicate that FOF modulates chemokine production via the suppression of NF-B activation independently of the replication of RSV (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The abilities of these antibiotics to inhibit the secretion of proinflammatory cytokines are thought to be mediated by inhibition of NF-B (3,13). Furthermore, pretreatment with erythromycin or clarithromycin has been reported to inhibit rhinovirus infection by suppressing the expression of virus receptors and reducing the rhinovirus-induced inflammatory cytokine response (14,31). Fosfomycin (FOF) is a structurally unique antibiotic that is chemically unrelated to any other known antimicrobial agent (16).…”
mentioning
confidence: 99%